Quality of maternal and newborn care around the time of childbirth in Luxembourg during the COVID‐19 pandemic: Results of the IMAgiNE EURO study. Issue 1 (18th December 2022) - Arendt, Maryse; Tasch, Barbara; Conway, Francesca; Lecomte, Aline; Covi, Benedetta; Mariani, Ilaria; Valente, Emanuelle Pessa; Lazzerini, Marzia; ,
Abstract: Objective: To investigate the quality of maternal and newborn care (QMNC) during childbirth in Luxembourg from women's perspectives. Methods: Women giving birth in facilities in Luxembourg between March 1, 2020, and July 1, 2021, answered a validated online WHO standards‐based questionnaire as part of the multicountry IMAgINE EURO study. Descriptive and multivariate quantile regression analyses were performed. Results: A total of 493 women were included, representing 5.2% of women giving birth in the four maternity hospitals in Luxembourg during the study period. Most quality measures suggested high QMNC, although specific gaps were observed: 13.4% ( n = 66) of women reported not being treated with dignity, 9.1% ( n = 45) experienced abuse, 42.9% ( n = 30) were not asked for consent prior to instrumental vaginal birth, 39.3% ( n = 118) could not choose their birth position, 27% ( n = 133) did not exclusively breastfeed at discharge (without significant differences over time), 20.5% ( n = 101) reported an insufficient number of healthcare professionals, 20% ( n = 25) did not receive information on the newborn after cesarean, and 41.2% ( n = 203) reported lack of information on newborn danger signs before discharge. Multivariate analyses highlighted higher reported QMNC indexes among women born outside Luxembourg and delivering with a gynecologist, and significantly lower QMNC indexes in women with the highest education levels and those delivering in the hospital offering some private services. Conclusions: Despite maternal reports suggesting an overall high QMNC in Luxembourg, improvements are needed in specific aspects of care and communication, mostly related to maternal autonomy, respect, and support, but also number and competencies of the health workforce. Synopsis: Women giving birth in Luxembourg during the 16 months of the COVID‐19 pandemic reported gaps in quality of maternal and newborn care around the time of childbirth.